Removal of p16INK4 Expressing Cells in Late Life has Moderate Beneficial Effects on Skeletal Muscle Function in Male Mice - Guzman, Steve D.; Judge, Jennifer; Shigdar, Shahjahan M.; Paul, Thomas A.; Davis, Carol S.; Macpherson, Peter C.; Markworth, James F.; Van Remmen, Holly; Richardson, Arlan; McArdle, Anne; Brooks, Susan V. (Frontiers in Aging, 2022)
Aging results in the progressive accumulation of senescent cells in tissues that display loss of proliferative capacity and acquire a senescence-associated secretory phenotype (SASP). The tumor suppressor, p16INK4A, which slows the progression of the cell cycle, is highly expressed in most senescent cells and the removal of p16-expressing cells has been shown to be beneficial to tissue health. Although much work has been done to assess the effects of cellular senescence on a variety of different organs, little is known about the effects on skeletal muscle and whether reducing cellular senescent load would provide a therapeutic benefit against age-related muscle functional decline. We hypothesized that whole-body ablation of p16-expressing cells in the advanced stages of life in mice would provide a therapeutic benefit to skeletal muscle structure and function. Treatment of transgenic p16-3MR mice with ganciclovir (GCV) from 20-26 months of age resulted in reduced p16 mRNA levels in muscle. At 26 months of age, the masses of tibialis anterior, extensor digitorum longus, gastrocnemius and quadriceps muscles were significantly larger in GCV-treated compared with vehicle-treated mice, but this effect was limited to male mice. Maximum isometric force for gastrocnemius muscles was also greater in GCV-treated male mice compared to controls. Further examination of muscles of GCV- and vehicle-treated mice showed fewer CD68-positive macrophages present in the tissue following GCV treatment. Plasma cytokine levels were also measured with only one, granulocyte colony stimulating factor (G-CSF), out of 22 chemokines analyzed was reduced in GCV-treated mice. These findings suggest that removal of senescent cells, through the ablation of p16-expressing cells, provide moderate and sex specific therapeutic benefits to muscle mass and function.